Targeting STAT3 Enzyme for Cancer Treatment - Arun, Sowmiya; Patel, Praveen Kumar; Lakshmanan, Kaviarasan; Rajangopal, Kalirajan; Swaminathan, Gomathi; Byran, Gowramma (Mini Reviews in Medicinal Chemistry, 2024)
A category of cytoplasmic transcription factors called STATs mediates intracellular signaling, which is frequently generated at receptors on cell surfaces and subsequently sent to the nucleus. STAT3 is a member of a responsible for a variety of human tumor forms, including lymphomas, hematological malignancies, leukemias, multiple myeloma and several solid tumor types. Numerous investigations have demonstrated constitutive STAT3 activation lead to cancer development such as breast, head and neck, lung, colorectal, ovarian, gastric, hepatocellular, and prostate cancers. It's possible to get a hold of the book here. Tumor cells undergo apoptosis when STAT3 activation is suppressed. This review highlights the STAT3 activation and inhibition which can be used for further studies.
Keywords: proliferation